2009
DOI: 10.1002/14651858.cd004126.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-2 adrenergic agonists for the prevention of cardiac complications among patients undergoing surgery

Abstract: Our study provides encouraging evidence that alpha-2 adrenergic agonists may reduce cardiac risk, especially during vascular surgery. Nonetheless, these data remain insufficient to make firm conclusions about their efficacy and safety. A large randomized trial of alpha-2 adrenergic agonists is therefore warranted. Additionally, future research must determine which specific alpha-2 adrenergic agonist should be used, and whether it is safe to combine them with other perioperative interventions (for example beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 180 publications
2
46
2
4
Order By: Relevance
“…Moreover, the patients randomized to TEA received the cardioprotective drug, clonidine, through their epidural catheter. This cardioprotective drug 19 was not administered to the control patients. The withdrawal of ␤-blockers in all study patients and the selective use of clonidine in the patients randomized to TEA may explain the large benefit of TEA on supraventricular arrhythmias found in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the patients randomized to TEA received the cardioprotective drug, clonidine, through their epidural catheter. This cardioprotective drug 19 was not administered to the control patients. The withdrawal of ␤-blockers in all study patients and the selective use of clonidine in the patients randomized to TEA may explain the large benefit of TEA on supraventricular arrhythmias found in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant intraoperative adverse effects in patients who had received intravenous Clonidine in our study. 14 There was minimal bleeding from the surgical site and the field was clear for the surgeon to operate. This parameter was assessed in our study by the surgeon.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it is suggested that more studies will be necessary to confirm its benefits and safety to use in conjunction with other perioperative interventions like ß-blockers. [26] Recently, a randomised, double-blind, multi-centre clinical trial with a sample of 10,010 patients from 135 hospitals distributed across 23 countries was performed, evaluating the effect of clonidine, placebo, and ASA status. The clonidine group received 200 µg orally 2 to 4 hours before the surgical procedure, and as a transdermal patch that released 200 µg/24 h of clonidine, which was replaced every 72 hours post-surgery.…”
Section: Discussionmentioning
confidence: 99%